Community Education through Local Culture Sawer Bridal - Ruhmawati, Tati; Wahyudin, Uyu; Sardin, Sardin; Setiawan, Ridwan; Rizqi, Muhammad Aris; Mulyo, Gurid Pramintarto Eko (Journal of Ecohumanism, 2024)
Background: In 2019, Indonesia saw a peak in HIV-AIDS cases with 50,282 reported, and West Java ranked third nationally with 37,205 cases. To address the rising trend, especially in Bandung, this study examines the impact of traditional "sawer" bridal educational videos on the knowledge and attitudes of prospective bridal couples about AIDS. Method: Using a one-group pre-test and post-test design without a control group, this quasi-experimental research involved 50 couples from Bandung. Participants took a pre-test, viewed health message videos about HIV-AIDS, and then took a post-test. Results: The results showed that respondents were between 20 and 35 years old. Among them, 56% were women, 42% had a bachelor's degree, and 54% worked in the private sector. The average knowledge score increased from 78.60 to 92.78, and the attitude score improved from 89.62 to 94.10. A paired T-test showed a significant difference (p-value = 0.001). Thus, traditional "sawer" videos effectively enhance AIDS awareness among brides and grooms. This indicates that education tailored to the cultural context can be more effective in increasing health awareness